The Effect of Business Process Automation On The Effectiveness of Employee Work at PT. Industri Kemasan Semen Gresik - Idham Achmad Faizi (Jurnal Indonesia Sosial Teknologi, 2024)
This study aims to identify factors that affect the effectiveness of employee work at PT. Semen Gresik Packaging Industry (IKSG) and formulate recommendations to improve the effectiveness of the work. This research uses quantitative methods with a descriptive approach. The results of multiple regression analysis show that process automation has a positive influence on the effectiveness of employee work at PT. IKSG. Each one-unit increase in process automation contributes to an increase in work effectiveness by 0.246 units assuming the other variables are fixed. The results of the t test show that the availability of backups significantly affects the effectiveness of employee work. Based on these findings, it can be concluded that process automation factors affect the effectiveness of employee work at PT. IKSG. From the results of this study, it is concluded that there is a significant positive influence of process automation on the effectiveness of employee work at PT. IKSG. Therefore, it is advisable to increase investment and attention to these factors in order to improve the effectiveness of employee work and overall organizational performance.